A Book Review – Digging Deeper into Action Research: A Teacher Inquirer’s Field Guide - Jim R. Carlson (Networks: An Online Journal for Teacher Research, 2015)
Digging Deeper into Action Research proves itself a handy companion for practitioners embarking on the journey of action research. The chapters are organized in logical order, beginning with a brief historical overview of teacher research and its critical contribution to the national dialogue on education. Dana frames educational research as highly contextualized, reminding readers that “outside experts,” those removed from the day-to-day operations of school, have historically set the terms for what counts as research in education (Cochran-Smith & Lytle, 1993).